CORRELATION RADIUS AND LARGE- SCALE EQUATION OF INHOMOGENEOUS LIQUID IN THE GRAVITATION FIELD - Abdikarimov, B. Zh. (Recent Contributions to Physics, 2008)
In this research work the temperature, gravitational field and the altitude dependence of correlation radius are investigated using the light diffusion method the results of the experiment are used in defining large-scale function of correlation radius of inhomogeneous liquid in the gravitationfield examined closely to critical temperature. Investigations showed that inhomogeneous systems in space examined closely to critical point are described as large-scale equations of homogeneous systems conditions which confirm the type of gravitational effect equations.
Keywords: correlation radius